Intestinal parasites in hemodialysis patients from developing countries: A systematic review and meta‐analysis. Issue 1 (5th December 2019) - Taghipour, Ali; Olfatifar, Meysam; Rostami, Ali; Foroutan, Masoud; Vasigala, VeneelaKrishnaRekha; Norouzi, Mojtaba
Abstract: Intestinal parasitic infection (IPI) is the main cause of gastrointestinal complications in hemodialysis patients due to their impaired immune systems. We conducted a systematic review and meta‐analysis to evaluate the prevalence and odds ratio (OR) of IPIs in this population. Relevant eligible studies were identified by searching the PubMed, Science Direct, Scopus, Web of Science, and Google scholar databases up to January 30, 2019. A random‐effects meta‐analysis model was used to estimate the pooled prevalence, OR, and 95% confidence intervals (CI). Twenty‐two studies, from Turkey, Iran, Brazil, Egypt, Saudi Arabia, Pakistan, and Malaysia met eligibility criteria for analysis, and included 11 using a case–control design (980 patients and 893 controls) and 11 studies using a cross‐sectional design (a total of 1455 participants). Cross‐sectional studies suggested that the pooled prevalence of IPIs in hemodialysis patients was 24% (95% CI, 14–36%; 307/1455). In studies using a case–control design, the pooled prevalence of IPIs in hemodialysis patients (30%, 330/980) was found to be significantly higher than controls (10%, 115/893) (OR, 3.40; 95%CI, 2.37–4.87). With respect to the parasites, Cryptosporidium spp. (OR, 4.49; 95%CI, 2.64–7.64) and Blastocystis sp. (OR, 4.03; 95%CI, 1.20–13.51) were significantly higher in hemodialysis patients compared to the controls. The current study revealed a high prevalence of IPIs in hemodialysis patients from countries in which the baseline prevalence of parasitic infection is high. We recommend that periodic screenings for IPIs in such countries should be incorporated into the routine clinical care of hemodialysis patients.